A conceptual approach of ordinary and extraordinary means of medical treatment from Islamic perspective - Malik, Mohammad Manzoor (s.n, 2012)
This research project is aimed at formulating an Islamic perspective on obligations of Muslims to seek medical treatment in regards to contemporary bio-ethical distinction between ordinary and extraordinary medical care. The study basis its finding on the Qur'an, Sunnah, jurisprudential works, writing of traditional scholars on the subject, contemporary fatwas, Islamic medical codes, and resolution of Islamic jurist-consultant bodies